An Analysis of Zach Sobiech's Personality as the Main Character in Clouds Movie - Kayla Gabriela Bit; Adria Vitalya Gemilang; Afria Dian Prastanti (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this analysis is to find out the main character, Zach Sobiech, personality in Clouds movie. The researcher discussed the personality and nature of the main character in the Clouds movie directed by Justin Baldoni and distributed by Disney+, which was released on October 16, 2020. This study contains the personality of Zach Sobiech in Clouds movie. The types of personality and its factors of Zach Sobiech are analyzed using the theory of Paul Costa and Robert McCrae. The analytical method used is the descriptive qualitative method. Data collection is done by repeatedly watching and analyzing the evidence from the dialogues and his actions in the movie and the analytical theory here is obtained from books from library research and the internet in the form of electronic books. The results of the analysis in this study indicate that Zach has 11 personalities and, four personality traits from Zach, namely, openness, conscientiousness, extraversion, and agreeable.